STUDENTS’ VIEWS ON HIGHER EDUCATION TRANSFORMATIONS CAUSED BY THE COVID-19 PANDEMIC: A COMPARATIVE STUDY FOR LATVIA AND UKRAINE - Usca, Svetlana; Malykhin, Oleksandr; Aristova, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The study’s primary purpose was to compare Latvian and Ukrainian students’ views on transforming traditional learning process connected with implementing infection control measures aimed at preventing the spread of coronavirus and their consequences on higher education in both countries. In this study, the total number of respondents consisted of 207 undergraduate, graduate and postgraduate students from Latvia and Ukraine. Latvian research sample was presented by 109 students including 11 male students (10.09%) and 98 female students (89.91%). Ukrainian research sample consisted of 98 students including 16 male students (16.33%) and 82 female students (83.67%). A convenience sampling technique was used for selecting the research sample. The survey was conducted in October 2020 - March 2021. The current research is carried out within the project of National Academy of Educational Sciences of Ukraine “Organization of Educational Process in the Content of Unpredicted Changes (the Covid-19 Pandemic): Comparative Analysis (Ukraine – EU countries)”, No. 0121U108690.